Sistem Bagi Hasil Mudharabah Sebagai Mekanisme Self Regulating terhadap Kenaikan Upah Minimum Regional Pada UMKM Puti Minang Group (PtM) - Wahyudi, Heru (Falah: Jurnal Ekonomi Syariah, 2019)
Conflicts regarding tariff transitions and wages often occur in Indonesia. On the other hand, SMEs have an important role in efforts to improve the welfare of the community. This study aims to discuss self-regulating the results (mudharabah) of regional minimum wage increases at the MSME Puti Minang Group (PtM) successfully overcoming wage conflicts with Mudharabah. This research is a skin research carried out at PtM MSMEs in 6 Regencies in Lampung Province. The processed data is primarily based on the data for the result in PtM. In general, profit sharing (Mudharabah) at PTM in 2016 exceeded regional minimum wages. Based on the output value, it can be seen that the P-Value = 0,000, means smaller than the value ? = 0.05, so Ho is rejected and accept Ha. For users (Mudharabah) of PTM in 2016 is greater than the UMR in 2016. PtM wage system using profit sharing (Mudharabah), can provide regional minimum wage standard (UMR) in Lampung in 2016, with an increase of 2016 UMR of 13% from UMR 2015. These results are evidence that a UMR increase of 13%, the profit-sharing system (Mudharabah) at PTM still has the ability to adapt (self-regulate) to the increase in UMR.